Solid state fermentation of brewers’ spent grains for improved nutritional profile using Bacillus subtilis WX-17 - Tan, Yong Xing (2020)
Brewers’ spent grains (BSG) are underutilized food waste materials produced in large quantities from the brewing industry. In this study, solid state fermentation of BSG using Bacillus subtilis WX-17 was carried out to improve the nutritional value of BSG. Fermenting BSG with the strain WX-17, isolated from commercial natto, significantly enhanced the nutritional content in BSG compared to unfermented BSG, as determined by the marked difference in the level of metabolites. In total, 35 metabolites showed significant difference, which could be categorized into amino acids, fatty acids, carbohydrates, and tricarboxylic acid cycle intermediates. Pathway analysis revealed that glycolysis was upregulated, as indicated by the drop in the level of carbohydrate compounds. This shifted the metabolic flux particularly towards the amino acid pathway, leading to a 2-fold increase in the total amount of amino acid from 0.859 ± 0.05 to 1.894 ± 0.1 mg per g of BSG after fermentation. Also, the total amount of unsaturated fatty acid increased by 1.7 times and the total antioxidant quantity remarkably increased by 5.8 times after fermentation. This study demonstrates that novel fermentation processes can value-add food by-products, and valorized food waste could potentially be used for food-related applications. In addition, the study revealed the metabolic changes and mechanisms behind the microbial solid state fermentation of BSG.